The ameliorative effect of Lactobacillus plantarum-12 on DSS-induced murine colitis. Issue 6 (27th May 2020) - Sun, Mengying; Liu, Yujun; Song, Yinglong; Gao, Yuan; Zhao, Fujunzhu; Luo, Yanghe; Qian, Fang; Mu, Guangqing; Tuo, Yanfeng
Abstract : Lactobacillus plantarum -12 can relieve colitis, and the results have some practical value in applications. Abstract : Some strains of lactobacilli can exert beneficial effects on a host when ingested in an adequate dose, such as immunoregulation and anti-inflammatory activities. In this study, the survival abilities under simulated gastrointestinal conditions, adhesion abilities on HT-29 cell monolayers, and hemolytic activities of four Lactobacillus plantarum strains were assessed. Among the four strains, L. plantarum -12 showed the higher survival rate under simulated gastrointestinal conditions and adhesion index on the HT-29 cell monolayers, exhibited γ-haemolytic activity and had no biological amine producing ability. L. plantarum -12 was administered to dextran sodium sulfate (DSS)-induced ulcerative colitis (UC) Balb/c mice by oral gavage for 10 days. It was observed that the UC Balb/c mice showed symptoms of colonic atrophy, intestinal histopathological change, gut microbial disturbance, and pro-inflammatory cytokine expression. L. plantarum -12 administration remarkably attenuated DSS-induced UC in mice . L. plantarum -12 administration could restore gut microbiota by increasing beneficial bacteria such as Lactobacillus and decreasing intestinal pathogenic bacteria like Proteobacteria. L. plantarum -12 administration could improve immunity via activating the janus kinase-signal transducer and the activator of the transcription (JAK-STAT) pathway and up-regulating adenosine deaminase (ADA) and interferon-induced protein with tetratricopeptide repeats 1 protein (IFIT1), and enforce the intestinal barrier function by up-regulating mucin 2 (MUC2) protein expression. In conclusion, L. plantarum -12 could attenuate DSS-induced UC in Balb/c mice by ameliorating intestinal inflammation, and restoring the disturbed gut microbiota. L. plantarum -12 could be used as promising probiotics to ameliorate colitis.